The Influence of Organizational Culture, Knowledge Management and Financial Compensation on Employee Performance (Literature Review of Human Resource Management) - Arisnani Zuleha; Faroman Syarief (Journal of Accounting and Finance Management, 2021)
In the face of increasingly fierce business competition along with the increasing progress of science and technology, it has an impact on changes in the business environment (companies and organizations). The changes that are happening right now are the result of globalization that has hit all countries in the world. To face business competition that is increasingly competitive, dynamic and difficult to predict, qualified human resources and experts in their fields are needed as well as a good management strategy within the company. The importance of integrating the company's vision and mission with human resource management in managing the business so that the company gets maximum profit and the company's business can continue to develop as good corporate governance. In the results of this literature review obtained regarding the factors that can affect the performance of employees in the company. These factors include: (1) Organizational Culture has an effect on Employee Performance (2) Knowledge Management has an effect on Employee Performance (3) Financial Compensation has an effect on Employee Performance.